A radon transform-based method for line spectrum enhancement of vector hydrophone LOFAR spectrograms under low SNR conditions - Jun Wang; Caixia Song; Zhiguo Qi (Scientific Reports)
Abstract A Line spectrum Enhancement method for LOw Frequency Analysis and Recording (LOFAR) spectrum based on the Radon transform (LELR) is proposed, which is to improve the ability of vector hydrophone spectral line extraction under low signal-to-noise ratio. The LELR method leverages the characteristic that, over long time periods, the line spectra in the LOFAR (Low-Frequency Analysis and Recording) spectrogram approximate straight lines. By exploiting this property, the problem of line spectrum enhancement is transformed into one of linear feature enhancement within the LOFAR spectrogram. This transformation significantly improves the automatic detection and feature recognition capabilities of vector hydrophones. Extensive simulation and sea field experiment results show that the LELR method can effectively solve all kinds of line spectrum problems in actual sea trial data, such as the enhancement and extraction of spectral lines with varying intensities, line spectrum deformation, line spectrum intermittence, even line spectrum damage, etc.